DESAIN RANSEL PENGHASIL LISTRIK DENGAN MEMANFAATKAN TENAGA GERAK BERJALAN MANUSIA - Aini Aini Lostari; R Yudi Hartono (MULTITEK INDONESIA, 2019)
Energy is something that cannot be separated from human life because every activity carried out requires and produces energy. From some energy sources, there are activities carried out by the human body which are the potential to produce energy that can be utilized. One of the human activities that are often done is walking and running so that from this movement energy sources can be created. In this study, the calculation and design of backpacks with changes in length variations, variations in spring constants, and optimization of generators to produce electrical energy are better. This research began by designing a backpack that generates electricity by utilizing the power of human walking. Then the determination of product requirements is related to gathering information and products to be designed. Information obtained from previous research journals. Next, a study was carried out on the design of a backpack related to the calculation of the frequency of human gait needed to move a backpack and the calculation of springs. In this study, the results obtained are the voltage generated when the human condition goes by 3.863 watts, and when the human condition goes upstairs by 4.56 watts, while the running condition is 5.39 watts. So that the more movements humans make, the higher the voltage generated. And the resulting spring constant value is Ktotal = 22,612 N / m, and for the unit spring constant is 11,306 N / m. While the magnitude of the force produced by the load is 17.48 N.